KAJIAN KEBIJAKAN PEMBANGUNAN DAN PENGEMBANGAN PARIWISATA PERIODE 2017-2025 DI KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Pedro Pedro; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2021)
The North Kuta District is a strategic area which is located in the suburb of Denpasar City and also borders South Kuta. Since 2011, North Kuta District has been planned as part of the urban development area of Sarbagita, which is a national strategic area in Bali island. The utilization of space in the North Kuta District has developed quite rapidly. This study uses documentary research methods with content analysis techniques in the form of official government documents in the form of Regional Regulations concerning the Master Plan for Tourism Development in Badung Regency (RIPPARKAB) and Regional Spatial Planning (RTRW) at the Badung Regency level. The result shows that The tourism development policy in North Kuta District has become a guide for stakeholders, starting from the government, private sector, and society. However, the orientation of tourism development achievement is determined only from the economic growth side. In terms of quantity, tourism is seen from the increasing number of tourist visits both foreign or domestic tourists. The quality depends on the length of stay of tourists and the number of tourist expenses. It was also found that there were obstacles in the regional regulations regarding RDTR, where for the Badung Regency only South Kuta District had been promulgated a regional regulation. North Kuta District is one of the other five sub-districts where there is no clarity regarding the RDTR. The government can immediately finalize the RDTR regulation so that implementation in North Kuta District can be following the plan. Keyword: tourism, tourism policy, development, Kuta Utara, Badung